2003
DOI: 10.5424/sjar/2003011-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation and potassium application in melon (Cucumis melo L.) production. II: Quality

Abstract: IntroducciónAl hablar de la calidad del fruto del melón, es frecuente que en la literatura se haga referencia exclusivamente al tamaño del mismo (Mannini, 1988;Ferrer et al., 1992;Pellicer et al., 1997). Otros autores consideran también como parámetros de calidad la relación entre la longitud y la anchura denominada índice de forma, ya que contribuye al aspecto que presenta el fruto y a la aceptación que tendrá en el mercado (Artés et al., 1993;Kuboi, 1994), el grosor de la pulpa ResumenEn este trabajo se est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Therefore, it is pF, as a lumped parameter of θ and EC se , that explains not only the effects of irrigation on melon yield, but also quality. Whatever the case, with 13.5 ± 0.2 ºBx (DI and SDI) and 14.3 ± 0.3 ºBx (FI), the SSC in all three treatments kept well above the standard SSC contents found in 'Piel de Sapo' melons in Spain and abroad, which lays between 10 and 13 ºBx (Ribas et al, 2003;Cabello et al, 2009;Dalastra et al, 2016). Similarly to SSC, the TA in all treatments with means between 1.17 and 1.29 mg/L, was still well within the standard range for 'Piel de Sapo' melons, which runs from 1.05 to 1.34 mg/L (Artés et al, 1993;Lázaro et al, 2012).…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, it is pF, as a lumped parameter of θ and EC se , that explains not only the effects of irrigation on melon yield, but also quality. Whatever the case, with 13.5 ± 0.2 ºBx (DI and SDI) and 14.3 ± 0.3 ºBx (FI), the SSC in all three treatments kept well above the standard SSC contents found in 'Piel de Sapo' melons in Spain and abroad, which lays between 10 and 13 ºBx (Ribas et al, 2003;Cabello et al, 2009;Dalastra et al, 2016). Similarly to SSC, the TA in all treatments with means between 1.17 and 1.29 mg/L, was still well within the standard range for 'Piel de Sapo' melons, which runs from 1.05 to 1.34 mg/L (Artés et al, 1993;Lázaro et al, 2012).…”
Section: Discussionmentioning
confidence: 64%
“…The water requirements quantified for the open field growing melon, depending on the climate of the area, varied between 4000 and 4500 m 3 ha -1 [40,41]. The difference in annual water requirements in this study highlights the increase in water productivity using irrigation scheduling based on soil water control, as compared to that based on crop coefficient estimation [20,42,43].…”
Section: Discussionmentioning
confidence: 92%
“…This underscores the need for recognizing the value of water in agriculture and making rational and sustainable use of it, through different measures to optimize its use and management, leading to an increase in the sustainability of irrigated agriculture [8,9]. The melon crop (Cucumis melo L.) would be considered as particularly sensitive to drought and water stress, as it would negatively affect vegetative growth and reduce the yield via fruit cracking [10], therefore assuming large economic losses. Spain is the main producer and exporter in the European Union, generating 63% of the European production, the amount of which totals a value of EUR 325 million [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Sensoy et al (2007) found that the highest yield was obtained from the treatment employing the greatest frequency and quantity of irrigation. In connection, Ribas et al (2001) stated that melon yield could significantly decrease by using less amount of water than recommended. Furthermore, Cabello et al (2009) found that moderate water stress (75% of Etc) did not reduce melon yield and with severe deficit irrigation, the yield was reduced by 22% which mainly due to decrease fruit weight.…”
Section: Fruit Yield and Yield Attributes And Fruit Quality Early And Total Fruit Yields Early Fruit Yieldmentioning
confidence: 99%
“…Nevertheless, Gil et al (2000) and Lei et al (2003) found that application of limited amounts of water may improve fruit quality and sometimes improve the yield compared with full irrigation. Moreover, Ribas et al (2001) stated that melon yield could significantly decrease by using less amount of water than recommended.…”
Section: Introductionmentioning
confidence: 99%